Pengaruh Konsep Pemerintahan Terhadap Pemenuhan Aspirasi Masyarakat - Tamaulina Br. Sembiring; Shabrina Malka Mj; Sarima Sihombing; Ali Imamta Muham; Muhammad Aulia Aditya Rahman Zebua; Bagus Riandi; Amanda Diyana Zahra; Muhammad Fariz Nasutio; Tubagus Aditya Wardana; Luthfi Alghifari Batubara; Davina Sarah Azzevi (PT PUSTAKA CENDEKIA GROUP, 2024)
The concept of government reflects the system of managing power in a country, which greatly influences the level of community involvement and providing for their needs. This article discusses the influence of various forms of government, such as democracy, monarchy, and authoritarianism, on the government's ability to fulfill people's aspirations. By analyzing theory and case studies in several countries, this article concludes that governments that provide participation and transparency are more effective in responding to people's aspirations than systems that limit the role of citizens